FREQUENCY ANALYSIS OF VIBRATIONS OF THE ROUND PARACHUTE EDGE - S. V. Zhurin; A. L. Polovnev (Научный вестник МГТУ ГА)
The article is addressed to the analysis of the videos obtained during flight experiment at the launch of meteo-rocket MMP-06 in order to determine main characteristics of the oscillatory process the edges of the canopy at subsonic speeds at altitudes from 42,2 km to 34.2 km. Data analysis demonstrated that the oscillations of the edge of the canopy has a random character. The structure frequency of 2.4 Hz was identified from the analysis to be determined by the nylon sling stiffness.